Regulatory affairs role in a multinational pharmaceutical company - Pinho, Bárbara Marina da Silva (2014)
The present monograph intends to present a Regulatory Affairs department at a Multinational Pharmaceutical Company, as well as the role of the professionals working in that department. The experience which led to this monograph occurred after the conclusion of the curricular part of the Masters in Pharmaceutical Medicine, and was an opportunity to apply all the knowledge previously acquired and to develop new technical and personal skills. After the contextualisation of this document, the first chapter of this monograph introduce the Regulatory Affairs Professionals describing their principal responsibilities inside of the team. Following this, the principal activities developed by these professionals are described as well as how they interact with the different stakeholders. After framing the professional and the tasks developed, the structure of the modern Regulatory Affairs department is introduced and its impact on a Pharmaceutical Company is analysed. The following chapters promote a more personal view, showing the main activities developed during this professional experience and how the knowledge acquired prior and during it influenced the achieved results.